12 years a slave - McQueen, Steve; Ejiofor, Chiwetel; Fassbender, Michael; Cumberbatch, Benedict ([place of publication not identified] : [publisher not identified], 2013)
Based on an incredible true story of the man's fight for survival and freedom. In the pre-Civil War United States, Solomon Northup, a free black man from upstate New York, is abducted and sold into slavery. Facing cruelt, as well as unexpected kindnesses, Solomon struggles not only to stay alive, but to retain his dignity. In the twelfth year of his unforgettable odyssey, Solomon's chance meeting with a Canadian abolitionist will forever alter his life.
The extraordinary true story of Solomon Northup.
Based on the true-story book Twelve years a slave by Solomon Northup.
Director of photography, Sean Bobbitt ; production designer, Adam Stockhausen ; editor, Joe Walker ; costume designer, Patricia Norris ; music by Hans Zimmer
Chiwetel Ejiofor, Michael Fassbender, Benedict Cumberbatch, Paul Dano, Paul Giamatti, Lupita Nyong'o, Sarah Paulson, Brad Pitt, Alfre Woodard.
Filmed on location in the States of Louisiana and in Jefferson Parish.
LPF: 18
Keywords: Northup, Solomon, -- 1808-1863? -- Drama; Slaves -- United States -- Drama; African Americans -- Drama; Biographical films; African American men in motion pictures